2018
DOI: 10.3390/polym10090946
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design and Sound Absorption Properties of Nitrile Butadiene Rubber-Polyurethane Foam Composites with Stratified Structure

Abstract: Sound absorbing composites with stratified structures, including double-layer and sandwich structures, were prepared through the combination of nitrile butadiene rubber (NBR) and polyurethane foam (PUFM). The effects of the thickness ratio of layers, different stratified structures and the variety of fillers on the sound absorption performance of the NBR-PUFM composites and the sound absorption mechanism were studied. The results show that the NBR-PUFM composite with a sandwich structure and thickness ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It could be easy to confirm that reasonable range of the porosity φ was (0,1) according to its definition, as shown in Equation (18). Meanwhile, it was reported by the present literatures [1][2][3][4][8][9][10][11][12][13][14] that normal possible boundary of the static flow resistivity σ was [10000, 50000], so the investigated range in this research was set to [1000,200000], as shown in Equation (19). Moreover, the optimization target was to achieve minimized differences between the sound absorption coefficient of the experimental data α a f , d p f and that of the theoretical data α t f , d p f , as shown in Equation (20).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 68%
See 3 more Smart Citations
“…It could be easy to confirm that reasonable range of the porosity φ was (0,1) according to its definition, as shown in Equation (18). Meanwhile, it was reported by the present literatures [1][2][3][4][8][9][10][11][12][13][14] that normal possible boundary of the static flow resistivity σ was [10000, 50000], so the investigated range in this research was set to [1000,200000], as shown in Equation (19). Moreover, the optimization target was to achieve minimized differences between the sound absorption coefficient of the experimental data α a f , d p f and that of the theoretical data α t f , d p f , as shown in Equation (20).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 68%
“…Polyurethane foam is considered a promising and prospective sound-absorbing material for its high porosity, low density, fine transparency, mature fabrication technology, low manufacturing cost, excellent machinability, and so on [1,2], which meets some special requirements in the fields of sound absorption and noise reduction [3,4]. Gwon et al [1] studied sound absorption behavior of the flexible polyurethane foam with distinct cellular structure, the research result of which indicated that the strong gelling catalyst could generate a high number of small cells for a better sound absorption property.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the obtained transfer matrixes for the porous metal, microperforated panel, and the cavity, total transfer matrixes TT for the investigated five composite structures can be derived by the Equations (16)- (20), respectively, which correspond to the sound absorbers in the Figure 1a-e. By this method, sound absorption coefficient α of the investigated composite structures can be calculated, as shown in Equation 21.…”
Section: Sound Absorption Coefficient Of the Composite Structurementioning
confidence: 99%